1127 Prevalence of gastrointestinal diseases in brazilian workers receiving sick leave benefits – a retrospective study. (24th April 2018) - Marineli, JS; Rodrigues, NC; Silva, VR; Cardillo, LAF; Ferreira, LR
Abstract : Introduction: Gastrointestinal diseases in Brazil can be responsible for work disability, making employees eligible to receive sick leave benefits. The aim of this study was to determine the gastrointestinal tract diseases causing the most frequent number of sick leave benefits from the National Institute of Social Security (INSS) and the profile of these workers to understand better the occurrence of these pathologies amongst workers. Methods: A retrospective study was conducted between January 2014 and February 2017. We selected 3260 patients diagnosed with gastrointestinal diseases, who had received temporary social security benefits from INSS. The samples were submitted to data collection including: sex, age, occupation, and international classification of diseases (ICD). Diseases with higher prevalence were analysed. Results: The study revealed that the most prevalent gastrointestinal disease included abdominal hernias (ICD K40-K42-K43) in 1328 workers, cholelithiasis (ICD K80) in 1298 patients, acute appendicitis (ICD K35) 634 cases. The results showed that 54% were males, with a mean age of 43 years. However, cholelithiasis affected mostly females. Amongst the hernias, the most prevalent was inguinal hernia followed by umbilical and ventral hernias. All of the workers received temporary sick-leave benefit, but only 0.05% had the benefit of disability retirement and 0.35% sick-leave benefit due to work-related accidents (associated with hernia). Discussion: The data obtained allowed us to evaluate that the most frequent gastrointestinal diseases associated with sick-leave benefits were those related to surgical management. The appearance of abdominal wall hernias may occur due to increased intra-abdominal pressure, associated with intense physical exertion made by some workers. Dietary habits are a risk factor for appendicitis, especially a diet with low fibre intake. Fatty foods, on the other hand, may influence the occurrence of cholelithiasis. These data may help understand the main factors associated with work disability due to gastrointestinal diseases.